Prevalência de alterações na tolerância à glicose em pacientes asmáticos em uso de glicocorticóides atendidos em ambulatório de hospital de referência em pneumologia da rede pública de saúde em Belém – Pará - COSTA, Arinaldo Das Dores (2022)
Many elements can lead to glicemic alterations like glucose intolerance and diabetis, the diagnosis of those elements give a better support for the prevention of those alterations. This study had as objective evaluate the glucose’s tolerance alterations prevalence in asthmatics patients whose make frequent use of glucocorticoid, taken care of on a pneumology reference ambulatory of a public hospital in Belém-PA, as well the clinical and epidemiologic aspects related to the referred pathologies. The analysis was made by a case control study, utilizing information from interviews and protocols, laboratorial analysis of fast glicemia and glucose’s oral tolerance test, total cholesterol and fractions; beyond the evaluation of the risk factors to metabholic syndrome. Between the 30 people whose selected to the study, we concluded that chronic utilization of glucocorticoid has no relation with the appearance of glicemia alterations. This project hás its relevance not only for medical community, neither for atshmatics in longterm corticotherapy, but also for any patient, in any circunstance or pathology that made a longterm utilization glucocorticoids, looking for a better life quality and for profilaxy of probably glicemic alterations.